2018
DOI: 10.1111/1755-5922.12438
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin, but not rivaroxaban, promotes the calcification of the aortic valve in ApoE−/− mice

Abstract: We showed that warfarin, but not rivaroxaban, could induce calcific valve degeneration in a mouse model of atherosclerosis. Both the treatments did not significantly affect the progression of atherosclerosis. Overall, these data suggest a safer profile of rivaroxaban on the risk of cardiovascular disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…According to cross-sectional studies, the amount of ingested phylloquinone or menaquinones was predictive of coronary artery calcification [56,57]. Rattazzi et al provided evidence that warfarin, a vitamin K antagonist, worsened aortic valve calcification in a mouse model of atherosclerosis [58]. Vitamin K supplements attenuated vascular calcification by suppressing Toll-like receptors in an atherosclerosis animal model [59].…”
Section: Introductionmentioning
confidence: 99%
“…According to cross-sectional studies, the amount of ingested phylloquinone or menaquinones was predictive of coronary artery calcification [56,57]. Rattazzi et al provided evidence that warfarin, a vitamin K antagonist, worsened aortic valve calcification in a mouse model of atherosclerosis [58]. Vitamin K supplements attenuated vascular calcification by suppressing Toll-like receptors in an atherosclerosis animal model [59].…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent studies have shown a high association of Warfarin therapy and the occurrence of aortic valvular calcification. 17,18 Warfarin leads to calcification influencing the synthesis and function of the matrix Gla-protein, which is otherwise an inhibitor of the calcification process. 16,18 Taking everything mentioned together, it might be that the haemodynamic and mechanical forces along with oxidized lipids and exogenous substances (e.g., bacterial lipopolysaccharides) transform calm VICs into activated VICs.…”
Section: Presence Of Metaplasiamentioning
confidence: 99%
“…Our study was motivated by previous reports which have implicated VKA treatment in increased atherosclerotic calcification, plaque formation, and renal microvasculature damage . Although robust clinical data on this “renovascular calcification hypothesis” are limited, its implications are considerable because millions of patients globally are treated with VKA for prevention of stroke/systemic embolism in atrial fibrillation .…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective analysis of prospectively collected routine healthcare data in the primary care setting, we examined the im- Our study was motivated by previous reports which have implicated VKA treatment in increased atherosclerotic calcification, plaque formation, and renal microvasculature damage. 6,8,16 Although robust clinical data on this "renovascular calcification hypothesis" are limited, its implications are considerable because millions of patients globally are treated with VKA for prevention of stroke/systemic embolism in atrial fibrillation. 2,17 Our clinical data support this hypothesis by showing a statistically significant excess in kidney function loss in VKA patients, although the absolute impact was only small.…”
Section: Discussionmentioning
confidence: 99%